Infrared limb emission measurements of aerosol in the troposphere and stratosphere - Griessbach, S.; Hoffmann, Lars; Spang, R.; von Hobe, M.; Müller, Rolf; Riese, M. (Copernicus, 2015)
Altitude resolved aerosol detection in the upper troposphere and lower stratosphere (UTLS) is a challenging task for remote sensing instruments. Here, we introduce a new method for detecting aerosol in the UTLS based on infrared limb emission measurements. The method applies an improved aerosol-cloud-index that indicates infrared limb spectra affected by aerosol and ice clouds. For the discrimination between aerosol and ice clouds we developed a new method based on brightness temperature difference correlations. The discrimination thresholds for the new method were derived from radiative transfer simulations (including scattering) and Michelson Interferometer for Passive Atmospheric Sounding (MIPAS)/Envisat measurements obtained in 2011. The method not only reliably separates aerosol from ice clouds, but also provides characteristic yet overlapping correlation patterns for volcanic ash and sulfate aerosol. We demonstrate the value of the new approach for volcanic ash and sulfate aerosol originating from the Grímsvötn (Iceland), Puyehue-Cordón Caulle (Chile) and Nabro (Eritrea) eruptions by comparing with Atmospheric Infrared Sounder (AIRS) volcanic ash and SO2 measurements.